2019
DOI: 10.1021/acs.iecr.8b06465
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Hydrodeoxygenation over a Reduced and Sulfided NiMo/γ-Al2O3 Catalyst

Abstract: Phenol hydrodeoxygenation over a commercial NiMo/γ-Al2O3 catalyst in a reduced and sulfided form was investigated. Crushed particles (0.165–0.315 mm) were employed to determine the intrinsic reaction kinetics in either case. The internal diffusion phenomena within the catalytic particle of commercial dimensions and forms were also studied, and the phenol effective diffusion coefficient and effectiveness factor for both forms of the catalyst were determined. The sulfided form was active to phenol conversion at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Smaller peaks at the bands at 970 and 1250 cm –1 , assigned to the C–O stretching of phenols and alcohols, were detected in upgraded bio-oils from the NiMo/Al 2 O 3 catalyst. Molybdenum plays an important role in Ni metallic to enhance the reduction of C–O in phenols to aromatics as well as alcohols to either alkenes or alkanes in the presence of hydrogen, but a less effect was observed for Co metallic. Therefore, from FT-IR qualitative analysis, the NiMo/Al 2 O 3 catalyst provided significant improvement of bio-oil deoxygenation relative to other catalysts at both temperatures investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller peaks at the bands at 970 and 1250 cm –1 , assigned to the C–O stretching of phenols and alcohols, were detected in upgraded bio-oils from the NiMo/Al 2 O 3 catalyst. Molybdenum plays an important role in Ni metallic to enhance the reduction of C–O in phenols to aromatics as well as alcohols to either alkenes or alkanes in the presence of hydrogen, but a less effect was observed for Co metallic. Therefore, from FT-IR qualitative analysis, the NiMo/Al 2 O 3 catalyst provided significant improvement of bio-oil deoxygenation relative to other catalysts at both temperatures investigated.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is also confirmed by the decline of peaks assigned to hydroxyl groups at around 3350 cm −1 concerning the deoxygenation of aliphatic alcohols to esters. From the results, liquefied bio-oil from biomass was upgraded by elimination of oxygen atoms from in Ni metallic to enhance the reduction of C−O in phenols to aromatics as well as alcohols to either alkenes or alkanes in the presence of hydrogen, 59 but a less effect was observed for Co metallic. Therefore, from FT-IR qualitative analysis, the NiMo/ Al 2 O 3 catalyst provided significant improvement of bio-oil deoxygenation relative to other catalysts at both temperatures investigated.…”
Section: Resultsmentioning
confidence: 99%
“…19 Additionally, the reduced NiMo catalyst was more active as compared to the sulfided catalysts. 19 On the other hand, Romero and colleagues applied the same sulfided (Ni or Co)Mo/Al 2 O 3 supported catalysts on 2-ethylphenol HDO and observed that both promoters improved the deoxygenation rate, where Ni only promotes the HYD route, while Co promotes both HYD and DDO routes. 20 Recently, Song et al applied an efficient CoMoS nanosulfide catalyst on p-cresol.…”
Section: Introductionmentioning
confidence: 98%
“…14 Templis and coworkers also studied phenol HDO over a sulfided and reduced NiMo catalyst. 19 They found that the commercial sulfided NiMo γ-alumina supported catalysts exhibited 90% selectivity for cyclohexane production and suggested that phenol HDO proceeded via two parallel pathways, DDO and HYD. 19 Additionally, the reduced NiMo catalyst was more active as compared to the sulfided catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation